Constitutive activity of the Arabidopsis MAP Kinase 3 confers resistance to Pseudomonas syringae and drives robust immune responses. (3rd August 2017) - Lang, Julien; Genot, Baptiste; Hirt, Heribert; Colcombet, Jean
ABSTRACT: Mitogen Activated Protein Kinases (MAPKs) are known to be important mediators of plant responses to biotic and abiotic stresses. In a recent report, we enlarged the understanding of the Arabidopsis thaliana MPK3 functions showing that the expression of a constitutively active (CA) form of the protein led to auto-immune phenotypes. CA-MPK3 plants are dwarf and display defense responses that are characterized by the accumulation of salicylic acid and phytoalexins as well as by the upregulation of several defense genes. Consistently with these data, we present here results demonstrating that, compared with wild type controls, CA-MPK3 plants are more resistant to the hemibiotrophic pathogen Pseudomonas syringae DC3000. Based on our previous work, we also discuss the mechanisms of robust plant immunity controlled by sustained MPK3 activity, focusing especially on the roles of disease resistance proteins.